Usaha Payet Sumbar : Dari Industri Rumah Tangga Menjadi Kampung Payet ( 2014 – 2023 ) - Qur'ataini, Tri; Fitrisia, Azmi (Jurnal Kronologi, 2024)
This research discusses the development of the Payet Sumbar business from a home industry to a Kampung Payet in Alai Parak Kopi Village, North Padang District, West Sumatra, in the period 2014 to 2023. The aim of this research is to find out how the West Sumatra Sequin business has developed from 2014 – 2023 and what is the economic impact generated by the Payet Sumbar business on the income of the people of Kampung Payet. This research uses historical methods which include heuristics, source criticism, interpretation and historiography. The results of this research show that the Payet Sumbar business has succeeded in combining traditional heritage with modern innovation, creating products that are aesthetic and meaningful. The development of this business proves that home industry can develop into a significant local economic center with the support of the community and government. Ultimately, in 2021, the Padang City government inaugurated one of the areas in the Alai Parak Kopi area as an area named "Kampung Payet" as a form of government support for this business. The Mayor of Padang, Hendri Septa, acknowledged the success of the local economy and the contribution of the Payet Sumbar business to the regional economy. This research also highlights the socio-economic impact in the form of increasing income and opening up employment opportunities for local residents, the majority of whom are girls and housewives.